Penggunaan Media Rak Telur Rainbow dalam Meningkatkan Hasil Belajar Matematika Materi Perkalian dan Pembagian Kelas II SD Negeri Karangasem 01 - Suyuti, Fadilah Wahyu; Ridlo, Lumaur; Riwanto, Mawan Akhir (Jurnal Pancar, 2018)
This study aims to determine the use of rainbow egg rack media in mathematics subject matter of multiplication and division, and analyze the increase in mathematics learning outcomes in multiplication and division material after going through the use of rainbow egg rack media for second grade students of SD Negeri Karangasem 01 in 2018. This type of research is a classroom action research. Based on the results obtained during the implementation of classroom action research, that the average student learning outcomes in the pre cycle of 32 students amounted to 62, increased to 67.5 in the first cycle and increased to 82.1 in the second cycle. The grade completeness in the pre cycle was 34%, increasing to 66% in the first cycle and 84% in the second cycle. It can be concluded that the learning outcomes of mathematics using rainbow egg rack media in second grade students of SD Negeri Karangasem 01 experienced an increase in multiplication and division material.